2007
DOI: 10.1002/rcm.2839
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular interchain reactions in bidesmosidic glycosides, a new insight into carbohydrate rearrangements induced by electrospray ionisation

Abstract: Glycoconjugates are a class of complex molecules that are widely distributed in the plant kingdom and in some marine organisms. This class of compounds has a wide range of biological activities such as anti-inflammatory, antimicrobial, antifungal, anticancer, antiulcer, and immunoenhancing actions.1-3 Some of them also show various toxic activities such as cytotoxic, hemolytic, cardiotoxic, and teratogenic. Among these compounds, steroidal and triterpenoid saponins have long been known as components of widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…6(A)). It has been reported that an internal sugar loss can occur in the MS n fragmentation of protonated α ‐hederin and other triterpenic saponins 27, 28. This unusual fragmentation was first described for oligosaccharides such as sialyl lewis and the flavonoid glycosides 29–34.…”
Section: Resultsmentioning
confidence: 97%
“…6(A)). It has been reported that an internal sugar loss can occur in the MS n fragmentation of protonated α ‐hederin and other triterpenic saponins 27, 28. This unusual fragmentation was first described for oligosaccharides such as sialyl lewis and the flavonoid glycosides 29–34.…”
Section: Resultsmentioning
confidence: 97%
“…Dal Piaz et al . investigated the [M + H] + ions of triterpenoid and steroidal bidesmosidic saponins (Dal Piaz et al, ). They proposed firstly that the processes of an interchain reaction proceed through the formation of an ion–dipole (neutral) complex intermediate (Tu et al, ; Chai et al, ; Sun, Chai, & Pan, ).…”
Section: Characteristic Fragmentation Patternsmentioning
confidence: 99%
“…Claeys et al analyzed flavonoid O-diglycosides and indicated that the degree of internal glucose residue loss was strongly dependent on the aglycone type (Cuyckens et al, 2001). Dal Piaz et al investigated the [M þ H] þ ions of triterpenoid and steroidal bidesmosidic saponins (Dal Piaz et al, 2007). They proposed firstly that the processes of an interchain reaction proceed through the formation of an ion-dipole (neutral) complex intermediate (Tu et al, 2009;Chai et al, 2012;.…”
Section: B Mclafferty-type Rearrangement Reaction In the Mass Spectrmentioning
confidence: 99%
“…In addition to glycosidic-bond cleavages, rearrangements resulting in internal residue loss have been described in the collisionally induced dissociation (CID) of protonated oligosaccharides and glycoconjugates. These rearrangements have been reported to result in the loss of internal monosaccharide or oligosaccharide units , which have been named “false” sugar sequence ions . Next to proton adducts, ammonium adducts have been reported to result in such rearrangement products .…”
mentioning
confidence: 99%